2020
DOI: 10.1021/acs.orglett.0c01741
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Catalyzed Trifluoromethoxylation of Alkyl Trifluoroborates

Abstract: A silver-catalyzed trifluoromethoxylation of alkyl trifluoroborates with trifluoromethyl arylsulfonate as the trifluoromethoxylation reagent has been reported for the first time. This reaction is performed under mild reaction conditions and has wide functional group compatibility. In addition, the mechanism of this site-specific trifluoromethoxylation is proposed as a radical pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Other moieties that can be introduced into the molecules of saturated boronic derivatives by radical processes include sulfone, trifluoromethoxy, and difluorothiomethoxy groups (Table 4). [145][146][147]…”
Section: Barluenga-valdés Cross-couplingmentioning
confidence: 99%
“…Other moieties that can be introduced into the molecules of saturated boronic derivatives by radical processes include sulfone, trifluoromethoxy, and difluorothiomethoxy groups (Table 4). [145][146][147]…”
Section: Barluenga-valdés Cross-couplingmentioning
confidence: 99%
“…To our delight, both alkylsilanes and alkylborates could be trifluoromethoxylated under the selectfluor/silver system. [28] Alkylsilanes required equivalent silver fluoride and more TFMS, while alkylborates need catalytic silver salts and less TFMS, which might attribute to the higher reactivity of alkylborates. Due to mild condition, the trifluoromethoxylation of alkylborates showed nice tolerance towards various functional groups, especially iodide, chloride and OTs (Scheme 14).…”
Section: Trifluoromethoxylation Of Alkylsilanes and Alkylboratesmentioning
confidence: 99%
“…Possible reaction mechanisms of silver-mediated oxidative trifluoromethoxylation of alkylsilanes were proposed to involve radical processes. Analogous trifluoromethoxylation of alkyl trifluoroborates 71 (Scheme 42) by TFMS 57 was achieved under silver-catalyzed conditions [136]. This reaction was performed in the presence of AgOTf (30 mol %) and Selectfluor in anisole at 30 °C.…”
Section: Trifluoromethyl Arylsulfonates (Tfms)mentioning
confidence: 99%
“…Silver-catalyzed trifluoromethoxylation reaction could be extended to alkyl trifluoroborates 71 containing functions like hydroxyl, cyano, nitro, amide, ketone, aldehyde, bromo, ether and ester groups. Analogous trifluoromethoxylation of alkyl trifluoroborates 71 (Scheme 42) by TFMS 57 was achieved under silver-catalyzed conditions [136]. This reaction was performed in the presence of AgOTf (30 mol %) and Selectfluor in anisole at 30 • C. Optimization experiments revealed that phenanthroline could promote this trifluoromethoxylation and 18-crown-6 was added as phase transfer catalysts to improve the solubility of KF and alkyl trifluoroborates 71 in anisole.…”
Section: Trifluoromethyl Arylsulfonates (Tfms)mentioning
confidence: 99%